Implementation of Bi’ah Lugawiyyah in Enhanching Student’s Arabic Language Skills at Universitas Islam Sultan Sharif Ali (UNISSA) Brunei Darussalam - Athiyah Laila Hijriyah; Muhajir Muhajir; Aleeya Humaira Badrisya (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The purpose of this study was to analyze the implementation of bi’ah lugawiyyah in the Faculty of Arabic Language, analyze the supporting and inhibiting factors of implementation, and analyze the role of bi’ah lugawiyyah in improving students’ Arabic language skills. This study used a descriptive qualitative approach and the subjects were lecturers and ten students of the Faculty of Arabic Language, Sultan Sharif Ali Islamic University, Brunei Darussalam. Data collection techniques used participatory observation, in-depth interviews, and documentation. The results of this study revealed that the implementation of bi’ah lugawiyyah in the Faculty of Arabic Language, Sultan Sharif Ali Islamic University, Brunei Darussalam, which includes the obligation to use Arabic in class, direct teaching methods (thariqah mubasyarah), and the Mahrajan al-Lughah al-Arabiyah program, has proven effective in improving students’ Arabic language skills, both listening skills (maharah istima’), speaking skills (maharah kalam), reading skills (maharah qira’ah), and writing skills (maharah kitabah). The supporting factors for implementing bi’ah lugawiyyah are a conducive educational environment, cooperation between students and lecturers, and competent educators. Furthermore, there are inhibiting factors such as minimal mastery of Arabic vocabulary and rules, lack of self-confidence, and difficulty understanding the material. The overall implementation of bi’ah lugawiyyah has a role in providing significant stimulus in forming authentic and natural Arabic language characters and habits among students.